2018
DOI: 10.1016/j.conb.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Neurocircuitry of aggression and aggression seeking behavior: nose poking into brain circuitry controlling aggression

Abstract: Aggression is an innate behavior that helps individuals succeed in environments with limited resources. Over the past few decades, neurobiologists have identified neural circuits that promote and modulate aggression; however, far less is known regarding the motivational processes that drive aggression. Recent research suggests that aggression can activate reward centers in the brain to promote positive valence. Here, we review major recent findings regarding neural circuits that regulate aggression, with an em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 56 publications
3
63
0
1
Order By: Relevance
“…Golden et al (2019) also provide additional support for the similarity of mechanisms underlying appetitive aggression and drug addiction. The authors showed that Drd1 neuron blockade decreases the expression of aggression seeking following an abstinence period, a behavior resembling relapse behavior in drug addiction, supporting their previous results (Golden et al, 2016(Golden et al, , 2017Aleyasin et al, 2018b;Golden and Shaham, 2018). A similar blockade of Drd1 neurons in the NAc has also been previously shown to impair the acquisition and expression of cocaineinduced conditioned place preference (Hikida et al, 2010).…”
Section: Review Ofsupporting
confidence: 73%
“…Golden et al (2019) also provide additional support for the similarity of mechanisms underlying appetitive aggression and drug addiction. The authors showed that Drd1 neuron blockade decreases the expression of aggression seeking following an abstinence period, a behavior resembling relapse behavior in drug addiction, supporting their previous results (Golden et al, 2016(Golden et al, , 2017Aleyasin et al, 2018b;Golden and Shaham, 2018). A similar blockade of Drd1 neurons in the NAc has also been previously shown to impair the acquisition and expression of cocaineinduced conditioned place preference (Hikida et al, 2010).…”
Section: Review Ofsupporting
confidence: 73%
“…In support of this, neuroimaging studies in human psychiatric patients, particularly those with personality disorders, describe structural and functional abnormalities in key reward-related regions like the striatum that are correlated with aggression [15,16]. Consistent with human studies, recent investigations utilizing animal models of aggression CPP have identified functional roles for both the nucleus accumbens (NAc) [17] and the lateral habenula (LHb) [9] in the reinforcing effects of aggression. Interestingly, the VMH itself has also been reported to control aggression-seeking behavior in an operant model, indicating that this nucleus is not simply functioning as an on/off switch for attack, but may integrate information from primary reward centers to reinforce aggressive behavior [6].…”
Section: Influences Of Motivation On Aggressionmentioning
confidence: 66%
“…Finally, recent studies reported roles of other cell-typespecific circuits in aggression reward, as assessed in the selfadministration and CPP procedures (Aleyasin et al, 2018a;Yamaguchi and Lin, 2018). These include estrogen-receptor ␣1expressing neurons of ventromedial hypothalamus (Falkner et al, 2016), dopamine transporter-expressing neurons of hypothalamic ventral premammillary nucleus projecting to supramammillary nuclei (Stagkourakis et al, 2018), and GABAergic projections from basal forebrain to lateral habenula (Golden et al, 2016).…”
Section: Appetitive Aggression Reward In Rodentsmentioning
confidence: 99%
“…We focused on the nucleus accumbens (NAc), which earlier research has implicated in aggression self-administration and CPP (Couppis and Kennedy, 2008;Golden et al, 2016;Aleyasin et al, 2018b). There has been a recent interest in the role of the mesolimbic dopaminergic circuit in controlling aggression reward (Flanigan et al, 2017;Aleyasin et al, 2018a;Yamaguchi and Lin, 2018), as dopaminergic projections from the ventral tegmental area (VTA) to the NAc modulate both aggression intensity (Yu et al, 2014) and NAc dopamine levels Miczek, 2000, 2007). Additionally, local dopamine receptor blockade decreases aggression-reinforced operant responding (Couppis and Kennedy, 2008).…”
Section: Introductionmentioning
confidence: 99%